The Fixation Method according to the Fracture Type of the Greater Trochanter in Unstable Intertrochanteric Fractures Undergoing Arthroplasty - Sun, Doohoon (Hip Pelvis, 2017)
PURPOSE: We conducted a study on patients who underwent hip joint arthroplasty because of unstable femur intertrochanteric fractures with greater trochanter bony fragments. After dividing patients into three groups depending on their fracture patterns, we evaluated the clinical and radiological outcomes of different operation methods applied to each of these groups. MATERIALS AND METHODS: Using Evan's classification, we defined an unstable intertrochanteric fracture as those characterized as stage 4 or 5. Of the 137 patients presenting with an intertrochanteric fracture with osteoporosis (bone mineral density, <−2.5) between March 2014 and October 2015, 63 met the eligibility criteria and were included in this study. Next, patients were divided into three groups based on their greater trochanter fracture patterns (discerned with three-dimensional computed tomography images); different fixation methods were applied to each group by a single orthopaedic surgeon. RESULTS: Taken as a whole, 50 out of 63 patients experienced no reduction in walking distance in their daily lives. Harris hip score increased from 74.8 to 85.7 point and we considered this a relatively good result. Radiologically, we observed complete bone union in 62 cases (98.4%); the lone exception was in a patient who experienced osteolysis. There were also 3 cases who removed greater trochanter reattachment device due to broken implant and 1 case of dislocation. CONCLUSION: The different fixation methods applied to three distinct groups with varying fractures patterns were successful in achieving proper reduction and fixation of greater trochanteric fractures. We also observed reduced bone union periods when arthroplasty was performed in patients with unstable intertrochanteric fractures. Lastly, we believe these approaches may also aid in achieving early ambulation and early rehabilitations.